2000
DOI: 10.1038/oby.2000.31
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Sleep Apnea and Electrocardiographic Disturbances in Morbidly Obese Patients

Abstract: ). In order to make comparisons between groups with different severities of sleep-disordered breathing, we classified the patients in four groups using the apnea-hypopnea index (AHI): Group 1, AHI 5 Ͻ 15 (n ϭ 10); Group 2, AHI 15 Ͻ 30 (n ϭ 10); Group 3, AHI 30 Ͻ 65 (n ϭ 14); Group 4, AHI Ն 65 (n ϭ 17). Results:A wide range of sleep-disordered breathing, ranging from AHI of 2.5 to 128.9 was found. Ninety-eight percent of the sample (n ϭ 51) had an AHI Ն 5 (mean ϭ 51 Ϯ 37), and 33% had severe sleep apnea with AH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
78
1
5

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(88 citation statements)
references
References 22 publications
4
78
1
5
Order By: Relevance
“…Thus, it is diffi cult to conclude whether actual prevalence of OSA in the LABS-2 cohort is closer to 53%, as determined in the entire cohort from a combination of assessment methods, or 81%, as determined in the subsample who had past-year AHI available. It is interesting to note that this prevalence of OSA in the subsample with past-year AHI is consistent with several small single-center studies that determined OSA status via PSG (prevalence range: 72-98%), [3][4][5][6][7][8] while the prevalence in the group without a known past-year AHI is in line with a large cohort study in which OSA prevalence (41%) was determined with a set of screening questions. 9 Self-reported PAP compliance (i.e., use among those with OSA), which was similar between participants with and without past-year AHI (83.0% and 81.2%, respectively), was higher than objectively determined compliance reported in the general population, which is between 40% and 60% one year after starting PAP.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Thus, it is diffi cult to conclude whether actual prevalence of OSA in the LABS-2 cohort is closer to 53%, as determined in the entire cohort from a combination of assessment methods, or 81%, as determined in the subsample who had past-year AHI available. It is interesting to note that this prevalence of OSA in the subsample with past-year AHI is consistent with several small single-center studies that determined OSA status via PSG (prevalence range: 72-98%), [3][4][5][6][7][8] while the prevalence in the group without a known past-year AHI is in line with a large cohort study in which OSA prevalence (41%) was determined with a set of screening questions. 9 Self-reported PAP compliance (i.e., use among those with OSA), which was similar between participants with and without past-year AHI (83.0% and 81.2%, respectively), was higher than objectively determined compliance reported in the general population, which is between 40% and 60% one year after starting PAP.…”
Section: Discussionsupporting
confidence: 88%
“…1 Although the reported prevalence of obstructive sleep apnea (OSA) in bariatric surgery patients has been highly variable (ranging from 41% to 98%), [2][3][4][5][6][7][8][9] it is clearly substantially higher than the 2% to 4% prevalence in the general adult population. 10,11 There is evidence to suggest that OSA is independently associated with increased risk of perioperative and postoperative complications, 12,13 including following bariatric surgery.…”
Section: S C I E N T I F I C I N V E S T I G a T I O N Smentioning
confidence: 99%
“…This could cause difficulties during peri-operative airway management (Mechanick, Kushner et al 2009) and presence of OSA has been shown in LABS study to increase 30 day operative mortality (Flum, Belle et al 2009) hence the importance of the diagnosis leading to more stringent perioperative care of these individuals. About 40% of obese patients suffer with OSA (Sood 2009) and the prevalence can be as high as 98% in the morbidly obese patients (Valencia-Flores, Orea et al 2000).…”
Section: Obstructive Sleep Apnoea (Osa)mentioning
confidence: 99%
“…93 OSAS is highly prevalent and debilitating in extremely obese adolescents and adults. 94 OSAS is a compelling indication for bariatric surgery because of the reliable improvement seen in adults after Bariatric surgery for pediatric extreme obesity TH Inge et al weight loss. To determine the effect of surgical weight loss on OSAS adolescents, polysomnograms have been performed before and after surgical weight loss.…”
Section: Cardiovascular Risksmentioning
confidence: 99%